(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The heritage of Abu Nasr al-Farabi is a spiritual treasure that has become an endless ocean of world philosophy. Despite the fact that many issues have been solved in the study of Al-Farabi’s heritage, there are a few things that need to be addressed. In this regard, if we pay attention to the phenomenon of Farabi studies in Kazakhstan, the research has been systematized by a number of scientific findings on the number of scientists. The main goal of this orientation is to explore the essence of Farabi’s spiritual space, to discover the essence of spiritual, scientific, humanistic doctrines, and to prove the core of the scientific truth. The article provides a comprehensive set of topical issues and problems of Farabi studies in Kazakhstan. Keywords: al-Farabi legacy, philosophy, Farabi study, methodology, spirituality, historical consciousness, intellectual traditions, national brand.